2011
DOI: 10.5372/1905-7415.0504.061
|View full text |Cite
|
Sign up to set email alerts
|

Original article. Work-related quality of life scale among Singaporean nurses

Abstract: Background: The Work-Related Quality of Life Scale (WRQLS) was developed for health-care workers in England but might be useful, if valid, in other parts of the world or for other professions. Objective: We test the construct validity and reliability of the WRQLS as applied to nurses in Singapore. Methods: A descriptive study was undertaken in 2009 on a sample of 811 nurses at the National University Hospital (NUH) of Singapore who had at least one year’s work experience. The WRQL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The job and career satisfaction dimension - the second largest underlying construct - overlapped with working conditions and control at work . Compared with the PCA by Zeng et al [19], the format for loading the 22 original items of the WRQOLS was quite consistent. For instance, factor 6 (items 8, 11 and 12) and factor 7 (items 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The job and career satisfaction dimension - the second largest underlying construct - overlapped with working conditions and control at work . Compared with the PCA by Zeng et al [19], the format for loading the 22 original items of the WRQOLS was quite consistent. For instance, factor 6 (items 8, 11 and 12) and factor 7 (items 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 89%
“…By referring to the representative item(s) in each factor and the foregoing PCA research on the WRQOLS [16,19], the seven factors were named: (1) General well-being , (2) Home-work interface , (3) Employee engagement , (4) Job and career satisfaction , (5) Stress at work , (6) Working conditions , and (7) Control at work . Internal consistency of the overall scale and subscales based on this model was satisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[121920] We observed that the “item 2” (“I feel able to voice opinions and influence changes in my area of work”) in CAW domain was weak due to a high “alpha if item deleted.” Removal of this item increased the reliability of the CAW sub-scale. Item two has been suggested for removal by previous studies also, although they used other analytical tools.…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, where English is the official language, the WRQLS is a proven reliable tool for assessing the quality of the worklife of nurses; the researchers who tested it there suggested applying it to other medical personnel in Asia, after translating it into Asian languages [16]. The tool was then translated into Chinese [as the Work-related Quality of Life Scale-2 (WRQLS-2)] and further developed for assessing the quality of worklife [17].…”
Section: Introductionmentioning
confidence: 99%